CCUS: The Road to Net-Zero - Humbul Suleman; Rizwan Nasir (Energies, 2023)
As the world continues to grapple with the pressing issue of climate change, the development and implementation of carbon capture, utilisation, and storage (CCUS) technologies are becoming increasingly important [...]